Biocompatibility evaluation of bacterial cellulose as a scaffold material for tissue-engineered corneal stroma - Zhang, Chen (2020)
In this work, biocompatibility of bacterial cellulose (BC) was assessed as the scaffold for corneal stroma replacement. Biocompatibility was evaluated by examining rabbit corneal epithelial and stromal cells cultured on the BC scaffold. The growth of primary cells was assessed by optical microscope, scanning electron microscope (SEM), and transmission electron microscope (TEM). Live/dead viability/cytotoxicity assay and CCK-8 assay were used to evaluate cell survival. BC was surgically implanted in vivo into a stromal pocket. During a 3-month follow-up, the biocompatibility of BC was assessed. We found that epithelial and stromal cells grew well on BC and showed a survival rate of nearly 100\\%. The SEM examination for both kinds of cell showed abundant leafy protrusions, spherical projections, filopodia, cytoskeletons, and cellular interconnections. The stromal cells cultured on BC arranged regularly. TEM observation revealed normal cellular microstructure and a tight adhesion to the BC membrane. In vivo observation confirmed the optical transparency of BC during 3-month follow-up. The results demonstrated that BC had good biocompatibility for the tissue engineering of corneal stroma.